Recovery of Palladium and Silver from Copper Sludge and Spent Petrochemical Catalysts via Effective Pyrometallurgical Processing - Hyunju Kim; Hyunsik Park; Joohyun Park (Metals)
Copper-containing sludge and spent petrochemical catalyst (SPC) were investigated for recovering palladium (Pd) and silver (Ag). Increasing the mixing ratio of alumina-based SPC leads to reduced recovery rates at 1500 °C. Specifically, as the SPC mixing ratio increases from 10% to 30%, the recovery rate of Pd and Ag sharply decreases to 62.1% and 91.0%, respectively. This is attributed to an increase in the slag viscosity as well as to the higher sulfur content in the metal phase by decreasing the CaO/Al2O3 ratio of the slag. An increase in the slag viscosity causes a decrease in the metal recovery, as it lowers the settling velocity of metal droplets, resulting in imperfect metal separation, i.e., an increase in physical loss. Additionally, the presence of sulfur at the slag–metal interface was found to reduce interfacial tension, facilitating the entrapment of copper droplets within the slag. This further hindered phase separation and contributed to an increase in physical loss. This study highlights that physical loss is more serious in metal recovery rather than chemical loss, which is dependent on the thermochemical solubility of the target metals in the slag. The results emphasize the need for the precise control of slag properties to maximize the metal recovery processes in conjunction with a mitigation of CO2 emissions.